Autophagy and Endoplasmic Reticulum Stress during Onset and Progression of Arrhythmogenic Cardiomyopathy - Mark Pitsch; Sebastian Kant; Corinna Mytzka; Rudolf E. Leube; Claudia A. Krusche (Cells, 2021)
Arrhythmogenic cardiomyopathy (AC) is a heritable, potentially lethal disease without a causal therapy. AC is characterized by focal cardiomyocyte death followed by inflammation and progressive formation of connective tissue. The pathomechanisms leading to structural disease onset and progression, however, are not fully elucidated. Recent studies revealed that dysregulation of autophagy and endoplasmic/sarcoplasmic reticulum (ER/SR) stress plays an important role in cardiac pathophysiology. We therefore examined the temporal and spatial expression patterns of autophagy and ER/SR stress indicators in murine AC models by qRT-PCR, immunohistochemistry, in situ hybridization and electron microscopy. Cardiomyocytes overexpressing the autophagy markers LC3 and SQSTM1/p62 and containing prominent autophagic vacuoles were detected next to regions of inflammation and fibrosis during onset and chronic disease progression. mRNAs of the ER stress markers Chop and sXbp1 were elevated in both ventricles at disease onset. During chronic disease progression Chop mRNA was upregulated in right ventricles. In addition, reduced Ryr2 mRNA expression together with often drastically enlarged ER/SR cisternae further indicated SR dysfunction during this disease phase. Our observations support the hypothesis that locally altered autophagy and enhanced ER/SR stress play a role in AC pathogenesis both at the onset and during chronic progression.